Fluorescence switching of natural fibers with in-situ formation of gold nanoclusters - Yu, Yong (2024)
Natural fibers are a class of thread-like bio-based materials with merits of favorable mechanical properties, low cost, and minimal environmental impact, etc. Endowing additional functionalities to natural fibers would further encourage greater utilization of these renewable materials. In this work, we present a new strategy to integrate ultrasmall (<3 nm) gold nanoclusters (AuNC) with coconut fibers (coir), which resulted in a unique fluorescence switchable composite material. Specifically, we demonstrate that the delignified, green-emissive coir can act as a heterogeneous reducing and nucleating agent to form luminescent AuNC. The immobilization of AuNC switches the intrinsic green emission of delignified coir into enhanced orange emission of the resultant composite material. Our further investigations suggest that the fluorescence switching is governed by the Förster resonance energy transfer (FRET) process despite their disparity in material type, morphology, and size. Several important parameters, such as the FRET efficiency (E), rate constant (kT), the Förster radius (R0) and the distance between donor-acceptor pair (RDA) were estimated to describe the FRET process. The distance-sensitive FRET process was also confirmed by varying the medium between the AuNC and delignified coir, which highlighted the potential uses in stimuli-responsive sensor applications. We expect that this strategy can be extended to rationally design functional nature-based materials from various sources.